MIKROANATOMI HEPAR MENCIT (Mus musculus) SETELAH PEMBERIAN KITIN PER-ORAL - Isdadiyanto, Sri (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT–The objective of the experiment was determines liver microanatomy and diet consumption n the Mus muscalus after give of chitin. This research used completely randomized design. There were fow concentration of chitin, 0 mg chitin per day; 1,3 mg chitin per day; 1,95 mg chitin per day; 2,6 mg chitin per day. Anova was used in data analysis and LSDT test in 57o level. The result of experiment indicated that the chitin was not cause alteration on liver microanatomy.Keywords: chittin, Mus musculus, liver microanatomy